QUIET FIRING AND SILENT FIRING FROM THE PERSPECTIVE OF INDONESIAN LABOR LAW - Achmad Benyamin Daniel; Lia Christine; Catharina Dewi Wulansari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Quiet firing and silent firing are emerging phenomena in employment, arising alongside the transformation of industrial relations in the digital and platform economy era. Quiet firing refers to a company's strategy of encouraging employees to resign without formal termination, while silent firing occurs when employees are "quietly forced out" through the neglect of their roles or psychological pressure. This article analyzes these two phenomena within the context of Indonesian labor law, with a comparison to the labor law systems in Singapore and the United States. An interdisciplinary approach is employed to review the juridical, social, economic, and psychological aspects affecting workers. The analysis results indicate that the lack of explicit regulation regarding quiet firing and silent firing creates a legal vacuum that potentially violates the principle of labor protection as stated in Article 27 paragraph (2) and Article 28D of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) and Law Number 13 of 2003 juncto Law Number 6 of 2023 concerning Job Creation. In the international context, ILO Convention No. 158 affirms that every termination of employment must have a valid reason and be carried out through due process. Therefore, this article recommends the establishment of new norms within national labor law to address these practices of concealed termination, as well as strengthening the mechanism for labor supervision based on social justice.